Housing Needs versus a Right to Housing in International, EU and National Legislation - Napiórkowska-Baryła, Agnieszka (Studia Warmińskie, 2018)
A need to own a home is universal and is crucial throughout one’s whole life. Housing needs if unsatisfied affect many areas of one’s life, especially among young people, who undertake important decisions that will weigh heavily on the whole society. Hence, many legal regulations – international, within the EU, or national ones – raise the question of the right to life in dignity, in adequate housing conditions. The most important of such documents are: the UN Universal Declaration of Human Rights, the International Covenant on Economic, Social and Cultural Rights, Charter of Fundamental Rights of the European Union, and Resolutions of the European Parliament. In Poland, issues pertaining to the housing rights are resolved in the Constitution of the Republic of Poland and in other acts of law. They contain provisions which oblige the state and local governments to activate aid mechanisms to ensure that economically weaker families (households) have their housing needs satisfied. However, given the difficult housing situation in Poland, it can be concluded that these measures are not sufficient.